2014
DOI: 10.1017/s1751731114001293
|View full text |Cite
|
Sign up to set email alerts
|

Localising livestock protein feed production and the impact on land use and greenhouse gas emissions

Abstract: Livestock farmers in Sweden usually grow feed grains for livestock but import protein feed from outside Sweden. Aside from the economic implications, some environmental issues are associated with this practice. We used life cycle assessment to evaluate the impact of local protein feed production on land use and greenhouse gas emissions, compared with the use of imported protein feed, for pig meat and dairy milk produced in Sweden. Our results showed that local production reduced greenhouse gas emissions by 4.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 20 publications
(33 reference statements)
0
29
0
Order By: Relevance
“…They concluded that feeding strategies have the potential to reduce environmental impacts. Sasu-Boakye et al (2014) found a reduction in GWP up to 4.5% and 11% for LU. Meul et al (2012) found a reduction in GWP up to 3%.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They concluded that feeding strategies have the potential to reduce environmental impacts. Sasu-Boakye et al (2014) found a reduction in GWP up to 4.5% and 11% for LU. Meul et al (2012) found a reduction in GWP up to 3%.…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, no other studies aimed to assess the environmental impact of replacing SBM with RSM in finishing pig diets, although some assessed the impact of replacing SBM with locally produced protein sources such as peas, lupines and rapeseed products (Eriksson et al, 2005;Meul et al, 2012;Sasu-Boakye et al, 2014). Eriksson et al (2005) found a reduction in GWP up to 13% and in EU up to 22%.…”
Section: Discussionmentioning
confidence: 99%
“…The system boundaries include land use for feed production but not land use associated with subsequent steps in the production chain. Land use requirements for feed production were based on a modified version of mainly local feed rations in Sasu-Boakye et al (2014), in which minor amounts of imported soymeal and dried beet pulp were substituted with locally sourced feed ingredients while maintaining the rations' nutritional values. The annual production of 1 kg protein in VG-dairy requires 41 m 2 of land, of which 40 % is grassland and 60 % cropland.…”
Section: Case Studiesmentioning
confidence: 99%
“…Replacing SBM with locally produced protein sources resulted in a reduction of global warming potential (GWP) up to 13% and of land use (LU) up to 11% (Eriksson et al 2005;Meul et al 2012;Sasu-Boakye et al 2014). Replacing SBM with rapeseed meal (RSM) resulted in a reduction of LU up to 12%, but did not change GWP and energy use (EU) (Van Zanten et al 2015a).…”
Section: Introductionmentioning
confidence: 99%